Navigating relationship dynamics, pregnancy and fatherhood in the Bukhali trial: a qualitative study with men in Soweto, South Africa - Norris, Shane A.; Draper, Catherine E.; Motlhatlhedi, Molebogeng; Mabasa, Jackson; Headman, Tshepang; Klingberg, Sonja; Pentecost, Michelle; Stephen J. Lye; Nyati, Lukhanyo H. (BMC, 2023)
Background: South Africa has a complex range of historical, social, political, and economic factors that have shaped fatherhood. In the context of the Bukhali randomised controlled trial with young women in Soweto, South Africa, a qualitative study was conducted with the male partners of young women who had become pregnant during the trial. This exploratory study aimed to explore individual perceptions around relationship dynamics, their partner’s pregnancy, and fatherhood of partners of young women in Soweto, South Africa. Methods: Individual, in-depth interviews were conducted with male partners (fathers, n = 19, 25–46 years old) of Bukhali participants. A thematic approach was taken to the descriptive and exploratory process of analysis, and three final themes and subthemes were identified: (1) relationship dynamics (nature of relationship, relationship challenges); (2) pregnancy (feelings about the pregnancy, effect of the pregnancy on their relationship, providing support during pregnancy; and 3) fatherhood (view of fatherhood, roles of fathers, influences on views and motivation, challenges of fatherhood). Results: While most male participants were in a committed (“serious”) relationship with their female partner, less than half of them were cohabiting. Most reported that their partner’s pregnancy was not planned, and shared mixed feelings about the pregnancy (e.g., happy, excited, shocked, nervous), although their views about fatherhood were overwhelmingly positive. Many were concerned about how they would economically provide for their child and partner, particularly those who were unemployed. Participants identified both general and specific ways in which they provided support for their partner, e.g., being present, co-attending antenatal check-ups, providing material resources. For many, the most challenging aspect of fatherhood was having to provide financially. They seemed to understand the level of responsibility expected of them as a father, and that their involvement and presence related to love for and connection with their child. Participants’ responses indicated that there were some changes in the norms around fatherhood, suggesting that there is a possibility for a shift in the fatherhood narrative in their context. Conclusions: These findings suggest that the complex array of factors influencing fatherhood in South Africa continue to play out in this generation, although promising changes are evident.
Keywords: Fathers; LMIC; Qualitative; SDG-3: Good health and well-being